Efek Tadasana Terhadap Sakit Pinggang dan Tulang Belakang - Artha, I Wayan Joni (JURNAL YOGA DAN KESEHATAN, 2018)
Tadasana is very effective to overcome lumbago and back pain. This movement is very simple, which resembles a standing mountain. Samasthiti is another name of this posture to refer to the movement as balanced, not moving to the left or right, firmly fixed immobile. Stand with both legs straight, backbone straight and both hands are beside the body with the palm facing the body. This article describes the correlation of tadasana movement with the anatomy of the body to people who experience back pain, including for those who experience chronic back pain. When this asana is done, the structure of the spine will change. The muscles and bones around the spine are stretched in such a way that the cells are restructured so that the movement is able to heal pain around the waist and backbone effectively. Stretching is able to restore the wrong cell structure is returned to normal. This movement is very well done by both parents, young and children.